2021
DOI: 10.1088/1758-5090/abfca8
|View full text |Cite
|
Sign up to set email alerts
|

A perfusable vascularized full-thickness skin model for potential topical and systemic applications

Abstract: A perfusable vascularized full-thickness skin model for potential topical and systemic applicationsTo cite this article: Sacha Salameh et al 2021 Biofabrication 13 035042 View the article online for updates and enhancements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…The vascularization studies carried out on microfluidic devices culminated in the engineering of networks of perfusable cellular microvessels, [260] which were realized by precisely controlling the vascular microenvironment cues in vitro. [295][296][297] In certain models, the survival of the surrounding tissue entirely depends on the nutrients supplied by these vessels. In 2016, Sobrino et al generated vascularized 3D microtumors in an "on-a-chip" platform.…”
Section: Tissue Vascularizationmentioning
confidence: 99%
“…The vascularization studies carried out on microfluidic devices culminated in the engineering of networks of perfusable cellular microvessels, [260] which were realized by precisely controlling the vascular microenvironment cues in vitro. [295][296][297] In certain models, the survival of the surrounding tissue entirely depends on the nutrients supplied by these vessels. In 2016, Sobrino et al generated vascularized 3D microtumors in an "on-a-chip" platform.…”
Section: Tissue Vascularizationmentioning
confidence: 99%
“…Recently, Salameh et al used 3D templating techniques to develop a vascularized FTSm that includes a more complex vasculature system than the previously described models [ 117 ]. The technique used to produce hollow channels inside the collagen matrix was similar to the work by Mori et al, using nylon wires [ 115 ].…”
Section: The Evolution Of Skin-on-a-chip Platformsmentioning
confidence: 99%
“…Finally, they proved that the system could be used as a tool for improving the skin-equivalents. More recently, Salameh et al 85 developed a vascularized skin equivalent with more complex blood vasculature, which represented a differentiated epidermis with physiological organization, three perfusable vascular channels, and a microvascular network connected to the macrovessels. They demonstrated that perfusion of the skin reconstructs and the presence of a complex vascular network could assess respective topical and systemic applications.…”
Section: Fabrication Approaches For Prevascularized Skinmentioning
confidence: 99%